Extracellular matrix: from atomic resolution to ultrastructure. - Vakonakis, I; Campbell, I (2007)
The extracellular matrix (ECM) is a highly organized multimolecular structure, essential for life in higher organisms. Although substantial high-resolution structural information is available for relatively small fragments of ECM components, the inherent difficulty in preparing and analyzing samples of large, fibrous polymers impedes structural efforts. Here, we review recent advances in understanding the structure of three important ECM components: collagen, fibrillin and fibronectin. Emphasis is placed on the key role of intermolecular interactions in assembling larger, microm scale, structures.